The Mobile Small RNAs: Important Messengers for Long-Distance Communication in Plants - Yan, Yan; Ham, Byung-Kook (Frontiers in Plant Science, 2022)
Various species of small RNAs (sRNAs), notably microRNAs (miRs) and small interfering RNAs (siRNAs), have been characterized as the major effectors of RNA interference (RNAi) in plants. Growing evidence supports a model in which sRNAs move, intercellularly, systemically, and between cross-species. These sRNAs can traffic cell-to-cell through plasmodesmata (PD), in a symplasmic manner, as well as from source to sink tissues, via the phloem, to trigger gene silencing in their target cells. Such mobile sRNAs function in non-cell-autonomous communication pathways, to regulate various biological processes, such as plant development, reproduction, and plant defense. In this review, we summarize recent progress supporting the roles of mobile sRNA in plants, and discuss mechanisms of sRNA transport, signal amplification, and the plant’s response, in terms of RNAi activity, within the recipient tissues. We also discuss potential research directions and their likely impact on engineering of crops with traits for achieving food security.